Perbandingan Analisis Konten Berbasis Aida Dengan Metrik Engagement Instagram: Studi Kasus @Malanggateway - Hafiz Nafi’uddin (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2026)
This study aims to analyze the effectiveness of @malanggateway's Instagram promotional content by comparing the AIDA (Attention, Interest, Desire, Action) model approach and factual engagement metrics from Instagram Insights. This study uses a descriptive quantitative method with a comparative approach, analyzing six paid advertising content selected through a purposive sampling technique during the period of January–December 2024. Engagement data includes metrics likes, comments, saves, shares, link clicks and reach, while AIDA scores were obtained through a questionnaire with 35 respondents. The three content with the highest engagement had an average score of 3.83 with an average AIDA score of 4.37, while the three content with the lowest engagement had a score of 0.50 with an average AIDA score of 4.33. The results show that although most content has a high AIDA score, this is not always directly proportional to actual engagement on Instagram. This finding suggests that the success of promotional content depends not only on the strength of the communication structure, but also on visual factors, upload time, and audience preferences. In conclusion, the AIDA model is effective as a content development framework, but it needs to be combined with social media metrics analysis for a more optimal marketing strategy.